Norcantharidin induces G2/M arrest and apoptosis via activation of ERK and JNK, but not p38 signaling in human renal cell carcinoma ACHN cells - Huang Shuaishuai; Tuergong Gulimire; Zhu Hangjie; Wang Xue; Weng Guobin; Ren Yu (Acta Pharmaceutica, 2021)
Renal cell carcinoma (RCC) is generally acknowledged as the most resistant primary malignancy unresponsive to conventional radiotherapy and chemotherapy treatments. Norcantharidin (NCTD), a therapeutic compound derived from medicinal plants, has been shown to trigger apoptosis, as well as antimetastatic and antioxidant activities in several tumor cells. However, NCTD’s mechanism of antitumor activity in the RCC cell line remains unclear. In this study, we report that NCTD led to a time- and dose-dependent inhibition of cell proliferation. It had also markedly induced apoptosis and G2/M phase cell cycle arrest in a dose-dependent manner by decreasing the expressions of pro-caspase-3, pro-caspase-9, cyclin B1, and pCDC25C while increasing active caspase-3, cleaved-PARP, P21, and pCDC2 levels. Interestingly, NCTD treatment provoked the phosphorylation of extracellular-regulated protein kinase (ERK) and c-Jun-N-terminal kinase (JNK), but not of p38 MAPK. Moreover, SCH772984 and SP600125, ERK and JNK inhibitors, respectively, could partially abolish NCTD-induced apoptosis and G2/M phase cell cycle arrest. Collectively, these findings suggest that NCTD might activate JNK and ERK signaling pathways, consequently inducing apoptosis and G2/M arrest through the modulation of related proteins. This study provided evidence that NCTD is a promising therapeutic drug for the treatment of RCC.